Risk Perception and Adherence to Precautionary Protocols; the Experience at the Height of the COVID-19 Outbreak in Nigeria - Ibrahim, Abdullahi Haruna; Ladan, Muhammad Awwal; Fatihu, Aisha; Umar, Abubakar Faruk; Aikawa, Hussaini Muhammad (REAL in Nursing Journal, 2022)
Aim: The study is aimed at examining COVID-19 personal risk perception and adherence to lockdown precautionary protocol during the peak of COVID-19 outbreak in Nigeria.Methodology: A descriptive cross-sectional study was adopted in which 4864 responses were retrieved between April to June 2020 through an online questionnaire to assess risk perception to COVID-19 in Nigeria. Information sought was on personal risk perception, frequency of lockdown protocol violations, general perception regarding COVID-19 lockdown in Nigeria, Pearson’s chi square and frequencies were examined from the data with SPSS version 25.Results: 55.3% were between the ages of 26-35 years, 59.2% were males, 61.2% were singles, and 80.9% lived in urban areas. About half, (54.6%) had moderate risk perception, 41.4% had high personal COVID-19 risk perception. Though 40.1% strictly adhered to the lockdown protocols, 71.7% of the respondents had a positive perception regarding the lockdown. Pearson’ chi-square revealed significant relationship between being 26-35 years old, being male, being married, having at least a bachelor’s degree, being Hausa, being a public servant and having a moderate to high COVID-19 risk perception (p>0.05).Conclusion: There was a good level of COVID19 personal risk perception in the majority of the Nigerian populace and although majority had a positive perception regarding lockdown as a precautionary measure to curtail the spread of COVID-19, less than half of the respondents adhered strictly to the lockdown protocols.